1991
DOI: 10.1142/s0192415x9100020x
|View full text |Cite
|
Sign up to set email alerts
|

Action of Oren-gedoku-to on Platelet Aggregation in Vitro

Abstract: Oren-gedoku-to is a Chinese medicine with hypotensive activity, hemostatic actions and the ability to augment cerebral blood flow. It is therefore expected to be useful in patients with hypertension and cerebrovascular accident (CVA). These effects of Oren-gedoku-to on platelet aggregation and coagulation-fibrinolysis were evaluated. A significant decline in platelet aggregation rate in both healthy control and patient plasma in response to Oren-gedoku-to was found. Maximal platelet aggregation time shortened,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Sekiya & Okuda (1982) showed it to be an inhibitor of leukotrienes and prostaglandin biosynthesis (attributed to one of its components, Scutellariae Radix, which contains baicalin and baicalein). Fushitani et al (1995) showed it to act as a scavenger of free radicals whilst Mori et al (1991) reported it to be an inhibitor of platelet aggregation (due to Coptidis Rhizoma and Phellodendri Cortex which affect the cyclic nucleotide metabolic system mainly through the action of Berberine). Wang et al (1997) reported it to be an attenuator of IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Sekiya & Okuda (1982) showed it to be an inhibitor of leukotrienes and prostaglandin biosynthesis (attributed to one of its components, Scutellariae Radix, which contains baicalin and baicalein). Fushitani et al (1995) showed it to act as a scavenger of free radicals whilst Mori et al (1991) reported it to be an inhibitor of platelet aggregation (due to Coptidis Rhizoma and Phellodendri Cortex which affect the cyclic nucleotide metabolic system mainly through the action of Berberine). Wang et al (1997) reported it to be an attenuator of IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that HLJDD showed potent inhibitory effects on platelet aggregation and thrombus formation via inhibiting the phosphorylation of phospholipase C and protein kinase B in mice [ 131 ]. It has been validated that HLJDD can inhibit platelet aggregation and thrombosis in patients with cerebral infarction [ 132 ] and the rat model of MCAO [ 133 ].…”
Section: Effects Of Hljdd and Its Bioactive Components On The Neuropa...mentioning
confidence: 99%
“…Huang-Lian-Jie-Du-Tang (HLJDT), a traditional Chinese medicinal prescription widely used in treating clinical stroke, is comprised of four common herbs, Rhizoma coptidis (Coptis chinensis Franch, Ranunculaceae), Radix scutellariae (Scutellaria baicalensis Georgi, Labiatae), Cortex phellodendri (Phellodendron amurense Rupr, Rutaceae) and Fructus gardeniae (Gardenia jasminoides Ellis, Rubiaceae), in a 3:2:2:3 proportion. In addition to having favorable effects on gastrointestinal disorders, acute liver injury and cardiovascular diseases, further evidence has indicated that HLJDT could have potential therapeutic effects on cerebral ischemia (Mori et al, 1991;Ohta et al, 1998;Takase et al, 1989;Wu et al, 2004). HLJDT has been used clinically to treat subjects suffering from stroke, sequelae of stroke or vascular dementia (Xu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%